THE IMPACT OF PROTEIN SUPPLEMENTATION ON HUMAN HEALTH: A LITERATURE REVIEW OF RENAL, HEPATIC, CARDIOVASCULAR AND GASTROINTESTINAL EFFECTS - Bartłomiej Czerwiec; Malwina Wojtas; Julia Skowrońska-Borsuk; Joanna Pergoł; Martyna Narożniak; Adam Borsuk; Adrianna Ewa Pękacka; Julia Borkowska; Zuzanna Krupa; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and purposeProtein is a key nutrient, especially for physically active individuals. The growing popularity of whey protein (WP) supplementation among athletes and fitness enthusiasts is driven by its benefits for muscle regeneration and metabolism. However, concerns arise regarding excessive and unmonitored intake, particularly its effects on kidney and liver function, gut microbiota, and cardiovascular health. This review aims to summarize current knowledge on the health impacts of WP, highlighting both benefits and risks.MethodsA literature review was conducted using PubMed, Scopus, and Google Scholar with terms such as “whey protein”, “adverse effects”, “liver toxicity”, “kidney function”, “gut microbiota”, and “cardiovascular health”. Priority was given to studies from the last decade, including clinical trials and systematic reviews.Brief description of the state of knowledgeWP supports muscle growth, insulin sensitivity, and satiety. It may positively affect cardiovascular health by increasing GLP-1 levels, which help reduce blood glucose, blood pressure, and body weight. Nonetheless, excessive intake may strain liver and kidney function, particularly in those with pre-existing conditions. Effects on gut microbiota are mixed while some studies show anti-inflammatory benefits, others suggest dysbiosis. A key issue is the lack of dosage standardization and individual consultation, increasing misuse risk.SummaryWP supplementation can offer health and performance benefits when used responsibly. Risks, especially for liver and kidneys, must be considered. Individualized guidance and more standardized research are essential to ensure safe and effective use.